Perbandingan Kadar Flavonoid Total Seduhan Daun Benalu Cengkeh (Dendrophthoe Petandra L.) pada Bahan Segar dan Kering - Susilowati; Nurlinda Sari, Iin (Jurnal Farmasi (Journal of Pharmacy), 2020)
Dendrophthoe petandra L. is a plant that attaches itself to cloves. in society, this plant is often considered a pest, even though this parasite plant can be used as a medicinal plant because it contains phytochemicals including flavonoids, terpenoids, tannins, alkaloids and saponins. Flavonoids are marker compounds that are responsible for the antioxidant and anticancer potential of clove parasite leaves. In the use of medicinal plants, people usually use simple extraction techniques with infusion. The aim of this study was to determine of total flavonoid levels ini leaf infusion of fresh and dry clove parasite leaves so as to provide information to the public on the proper preparation of ingredients before use. Identification of flavonoids using the alkaline test with NaOH, acid test with H2SO4 and willstater test. Determination of total flavonoid levels was carried out by UV-Vis spectrophotometry using AlCl3 and expressed as quercetin equivalent. The results showed that clove parasite leaves contained flavonoids with total flavonoid levels of 8,1977 ppm QE of fresh leaf infusion and 5,4407 ppm QE of dry leaf infusion. Comparison analysis of levels with One Way Anova showed that the total flavonoids of fresh clove parasite leaves were significantly greater than the dry leaves.